Correlation Between Digital-Based Learning Tools and Interest in Learning Indonesian Students of Class VI of UPT SDN 060849 West Medan - Arpah, Juni; Sutikno; Rahmat Kartolo; Ramadhani, Julia; Mevy Sitorus, Ruth (PT Inovasi Pratama Internasional, 2026)
This study aims to analyze the correlation between digital-based learning tools and the interest in learning Indonesian among sixth-grade students at UPT SDN 060849, Medan Barat District, Medan City. The research method used is a quantitative approach with an associative research type. The research sample consisted of 31 students selected using a sampling technique based on the Isaac and Michael formula. The research instrument was a questionnaire whose validity and reliability had been tested using SPSS 22. The results of the validity test showed that 16 questions related to learning tools and 18 questions related to learning interests were declared valid. The reliability test using the Cronbach Alpha technique showed a value of 0.818 for learning tools and 0.899 for learning interests, which are categorized as very high. The results of the descriptive analysis showed that 53% of students agreed that the classroom had sufficient lighting, and 76% of students strongly agreed that the cleanliness of the classroom made them comfortable in learning. In addition, 59% of students strongly agreed that the classroom was always cleaned every day. In terms of learning interests, 71% of students showed a high interest in digital-based learning. The results of the hypothesis test using simple linear regression showed an r value of 0.654 and a coefficient of determination (R²) of 42.8%, indicating that digital-based learning tools have a positive and significant correlation with interest in learning Indonesian. Therefore, the better the digital facilities available, the higher the student's interest in learning. This study recommends improving digital tools in schools to optimize the Indonesian language learning process and providing teacher training in the use of educational technology